2020
DOI: 10.3758/s13414-020-02159-z
|View full text |Cite
|
Sign up to set email alerts
|

Distractor suppression leads to reduced flanker interference

Abstract: Recent studies using the additional singleton paradigm have shown that regularities in distractor locations can cause biases in the spatial priority map, such that attentional capture by salient singletons is reduced for locations that are likely to contain distractors. It has been suggested that this type of suppression is proactive (i.e., occurring before display onset). The current study replicated the original findings using an online version of the task. To further assess the suppression of high-probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
(96 reference statements)
2
13
0
Order By: Relevance
“…Experiment 1 was conducted using an online platform ( Pavlovia.org ) during a period when in-person testing was halted due to COVID-19. The online platform was validated by a recent publication that revealed LPL in online testing (Ivanov & Theeuwes, 2021 ). In addition, we conducted a pilot experiment to validate online testing.…”
Section: Methodsmentioning
confidence: 99%
“…Experiment 1 was conducted using an online platform ( Pavlovia.org ) during a period when in-person testing was halted due to COVID-19. The online platform was validated by a recent publication that revealed LPL in online testing (Ivanov & Theeuwes, 2021 ). In addition, we conducted a pilot experiment to validate online testing.…”
Section: Methodsmentioning
confidence: 99%
“…These findings indicate that the high-probability location was suppressed relative to the other display locations, attenuating the salience signal of stimuli presented at that location (Ferrante et al, 2018;Ivanov & Theeuwes, 2021;Wang & Theeuwes, 2018b, 2018a. Presumably, the weights within the spatial priority map, based on which attention is deployed, were adjusted so that the high-probability location was assigned a low priority to prevent distractor capture (Ferrante et al, 2018;Ivanov & Theeuwes, 2021;Wang & Theeuwes, 2018a, 2018b. Further research demonstrated that distractor location learning is modulated not only by learning of spatial, but also of nonspatial distractor regularities (Failing et al, 2019;van Moorselaar et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Second, when the target was presented at the high-probability location of the distractor, target selection was impaired (but see Allenmark et al, 2019;van Moorselaar et al, 2021). These findings indicate that the high-probability location was suppressed relative to the other display locations, attenuating the salience signal of stimuli presented at that location (Ferrante et al, 2018;Ivanov & Theeuwes, 2021;Wang & Theeuwes, 2018b, 2018a. Presumably, the weights within the spatial priority map, based on which attention is deployed, were adjusted so that the high-probability location was assigned a low priority to prevent distractor capture (Ferrante et al, 2018;Ivanov & Theeuwes, 2021;Wang & Theeuwes, 2018a, 2018b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, trial frequencies have often been varied across conditions to explore a variety of cognitive processes by investigating their interactions with probability (e.g., Broadbent & Gregory, 1965;Den Heyer, Briand, & Dannenbring, 1983;Miller & Pachella, 1973;Sanders, 1970;Theios, Smith, Haviland, Traupmann, & Moy, 1973). Currently, trial frequencies are commonly varied in studies of spatial and temporal statistical learning (e.g., Flowers, Palitsky, Sullivan, & Peterson, 2021;Gibson, Pauszek, Trost, & Wenger, 2021;Liesefeld & Müller, 2021;Vadillo, Giménez-Fernández, Beesley, Shanks, & Luque, 2021), the modulation of attentional control processes by environmental contingencies (e.g., Cochrane, Simmering, & Green, 2021;Huang, Theeuwes, & Donk, 2021;Kang & Chiu, 2021), action-outcome contingency learning (e.g., Gao & Gozli, 2021), adaptation to the frequency of congruent versus incongruent information (e.g., Bausenhart, Ulrich, & Miller, 2021;Ivanov & Theeuwes, 2021;Thomson, Simone, & Watter, 2021), and between-task resource sharing (e.g., Miller & Tang, 2021), to name just a few areas. Unfortunately, median bias is still sometimes overlooked and may contaminate published comparisons of conditions with different POWER OF MEDIAN RTS 8 trial frequencies (e.g., Bulger, Shinn-Cunningham, & Noyce, 2021).…”
Section: Type I Error Ratesmentioning
confidence: 99%